The Lambkins - Bunting, Eve, , 1928- (Joanna Cotler Books, 2005)
After being kidnapped by the lonely widow of a brilliant geneticist, Kyle finds himself shrunk to doll-size and living with three other children in a dollhouse from which there seems to be no escape